The Attitude and Translation Techniques on Public Sign - Sipayung, Kammer Tuahman; Silitonga, Harpen; Pasaribu, Yessi Octaviana; Ndraha, Libertini Priskila (Universitas Negeri Makassar, 2025)
Abstract. Public signs play a crucial role in the reader because they invite various issues from across cultures. Some research aims of this study try to describe the attitude (affect, judgment, and appreciation) in the source text and target text and translation techniques used by translators in translating public signs. This research is categorized as qualitative research type, to achieve the first aim the researcher applies the SFL approach. The data of this study is a pair of translations (public signs) in the form of phrases and clauses. The instruments used in this study are a camera (mobile phone) and an observation sheet. The researchers apply the theory of appraisal (Martin & White, 2005) and translation techniques (Molina and Albir, 2012). The total data for this study are 34 pairs of translations. The major result showed that, 1) the attitudinal in the source text (affect:7,40%, judgment: 59.2%, appreciation: 33.33% ) however, in the target text (affect:7.1%, judgment: 50%, appreciation:42.8%) 2) the translation techniques (literal translation: 68.75%, Reduction: 12.5%, Amplification: 9.3% and modulation: 9.3%). As the implication of this study, a shift can be occured to keep the better attitude from ST to TT. Keywords: Attitude, Translation techniques, Public sign